Rasio Low Density Lipoprotein dan High Density Lipoprotein pada Preeklamsi Berat dibandingkan dengan Kehamilan Normal di Rumah Sakit Dr. Hasan Sadikin Bandung - Amran Amrullah; Budi Handono; Akhmad Yogi Pramatirta (Indonesian Journal of Obstetrics & Gynecology Science, 2019)
AbstractObjective: This study aims to distinguish level of  (LDL/HDL)  and Low Density Lipoprotein/High Density Lipoprotein  ratio in severe preeclampsia patient compared to normal pregnancy.Method:  The study design was comparative cross-sectional study with consecutive sampling method that compared the laboratory results of LDL, HDL and ratio LDL/HDL that met the inclusion criteria. Subjects of this study were severe preeclampsia and normal pregnancy patient that fulfilled the inclusion criteria (n=60) in Dr. Hasan Sadikin General Hospital Bandung during August-September 2017.Result: It is revealed that the differences in level of LDL and LDL/HDL ratios in both groups were significant with p value ≤ 0,05. But there were no differences in HDL level. Increased level of LDL/HDL ratio in pregnancy was related to increased risk of preeclampsia with cut-off point> 2,632. If the increased level of LDL/HDL above cut-off point then the insident of severe preeclampsia increased 21,36 times.Conclusion: It was concluded that level of LDL and LDL/HDL ratios in severe preeclampsia were higher than in normal pregnancy. The increased LDL/HDL ratio of > 2.632 increased the risk of severe preeclampsia by 21.36 times.Perbandingan Rasio Low Density Lipoprotein/High Density Lipoprotein antara Preeklamsi Berat dan Kehamilan Normal di RSUP Dr. Hasan Sadikin BandungAbstrakTujuan: Penelitian ini adalah untuk mencari perbedaan rasio Low Density Lipoprotein/High Density Lipoprotein (LDL/HDL) pada preeklamsi berat dibandingkan dengan kehamilan normal sebagai faktor risiko timbulnya preeklamsi.Metode: Rancangan penelitian kasus kontrol membandingkan LDL, HDL, dan rasio LDL/HDL penderita preeklamsi berat dan kehamilan normal (n=60) bulan Agustus-September 2017 di Rumah Sakit Dr. Hasan Sadikin Bandung.Hasil: Hasil penelitian didapatkan perbedaan kadar LDL dan rasio LDL/HDL pada kedua kelompok secara bermakna dengan nilai p ≤0,05. Namun tidak didapatkan perbedaan yang bermakna pada kadar HDL. Peningkatan kadar LDL dan rasio LDL/HDL berhubungan dengan peningkatan risiko terjadinya preeklamsi dengan nilai cut-off > 2,632. Bila terjadi peningkatan rasio LDL/HDL diatas nilai cut-off maka risiko tejadinya preeklamsi berat sebesar 21,36 kali.Simpulan: Kadar LDL yang tinggi dan nilai cut-off rasio LDL/HDL >2,632 meningkatkan risiko terjadinya preeklamsi berat 21,36 kaliKata kunci: Preeklamsi, LDL, HDL, Rasio LDL/HDL